Chief and Copper - G.F. MacDonald Collection (1972)
Hereditary Gitxsan chief, David Gunanoot, with White Owl Copper. David is the son of famous fugitive and folk hero, Simon Gunanoot who evaded RCMP and Pinkerton men for 13 years and was later aquited of the charges. His father's story is told in a book by David Ricardo Williams, Trapline Outlaw: Simon Peter Gunanoot.